Development of the microwave Hall effect technique using an ESR spectrometer and a network analyser - 나병기; Kelly, S. L.; Vannice, M. A.; Walters, A. B. (IOP PUBLISHING, 1991)
An electron spin resonance (ESR) system was modified to conduct microwave Hall effect (MHE) measurements, but the ESR capability of the system was fully retained using interchangeable equipment. An X-band microwave frequency, a square-law detector, and phase-sensitive detection of the ESR signal were utilized during the modification. The ESR cavity was replaced with a bimodal MHE cavity and source modulation was used instead of field modulation. A cancelling channel was added to cancel out the non-ideal power at the secondary mode. A vector network analyser was used to tune the cavity and to measure the mobility of high mobility samples. A bimodal TE112 cylindrical cavity and a TE102 rectangular cavity were designed and constructed, and both gave good results. Silicon semiconductor samples, which had previously been well characterized, were used to calibrate the system and calculate the calibration constants.